Minimizing seabird by‐catch in industrial fisheries. (9th December 2014) - Boyd, C.
<x xml:space="preserve">Abstract</x> Read the Feature Paper: Significant reductions in mortality of threatened seabirds in a South African trawl fishery; other Commentaries on this paper: Challenges in seabird by‐catch mitigation and the Response from the authors: Problems and solutions for seabird bycatch in trawl fisheries